2018
DOI: 10.7717/peerj.4205
|View full text |Cite
|
Sign up to set email alerts
|

On the exponent in the Von Bertalanffy growth model

Abstract: Von Bertalanffy proposed the differential equation m′(t) = p × m(t)a − q × m(t) for the description of the mass growth of animals as a function m(t) of time t. He suggested that the solution using the metabolic scaling exponent a = 2/3 (Von Bertalanffy growth function VBGF) would be universal for vertebrates. Several authors questioned universality, as for certain species other models would provide a better fit. This paper reconsiders this question. Based on 60 data sets from literature (37 about fish and 23 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…However, catch data for fish seem not to support this statement. The authors [17] investigated a set of 60 data for different species (37 for fish) and fitted Equation (1) with the exponent b = 1 (generalized von Bertalanffy model). They found that for 17 of 37 fish-data, but only for one non-fish species, any exponent a could be used to model mass-growth without affecting the fit to the data significantly (when the other free parameters p, q, m 0 were optimized).…”
Section: Shape Of the Growth Curvesmentioning
confidence: 99%
“…However, catch data for fish seem not to support this statement. The authors [17] investigated a set of 60 data for different species (37 for fish) and fitted Equation (1) with the exponent b = 1 (generalized von Bertalanffy model). They found that for 17 of 37 fish-data, but only for one non-fish species, any exponent a could be used to model mass-growth without affecting the fit to the data significantly (when the other free parameters p, q, m 0 were optimized).…”
Section: Shape Of the Growth Curvesmentioning
confidence: 99%
“…The von Bertalanffy equation is a logistic model widely applied to describe the growth of different types of populations [32][33][34].…”
Section: Examplementioning
confidence: 99%
“…The Von Bertalanffy equation is a logistic model widely applied to describe growth of different types of populations [27][28][29].…”
Section: Examplementioning
confidence: 99%